THE IMPLEMENTATION OF PERSONALITY TRAITS THROUGH ZODIAC SIGN TO TEACH WRITING DESCRIPTIVE TEXT TO THE SEVENTH GRADE STUDENTS OF SMP NEGERI 1 KAMAL (RETAIN, 2014)
Abstrak Menulis adalah salah satu keterampilan penting yang harus dikuasai oleh siswa dalam mempelajari bahasa. Keterampilan ini digunakan untuk menyampaikan ide atau gagasan dalam bentuk tertulis. Lebih jauh lagi, menulis dianggap sebagai keterampilan yang paling sulit diantari keterampilan lain dalam Bahasa Inggris. Proses menulis sering membuat siswa mudah bosan. Dalam hal ini guru diharapkan mampu meningkatkan motivasi siswa agar tetap tertarik untuk menulis. Zodiac sign adalah media yang dapat digunakan untuk mengajar menulis. Di dalam media ini terdapat kosa kata tentang ciri kepribadian seseorang dan gambar menarik yang dapat meningkatkan motivasi siswa di kelas. Penelitian ini bertujuan untuk mendeskripsikan implementasi dari ciri kepribadian seseorang melalui Zodiac sign dalam menulis descriptive oleh kelas tujuh, respon siswa, dan hasil menulis siswa. Penelitian ini merupakan jenis penelitian deskriptif kualitatif dan menggunakan observasi, wawancara, dan tugas menulis siswa untuk mendapatkan data. Data penelitian merupakan hasil deskripsi yang dijelaskan berdasarkan tujuan penelitian. Setelah melakukan observasi, peneliti mendeskripsikan tiga hasil penelitian. Hasil penelitian pertama menunjukkan bahwa implementasi ciri kepribadian seseorang melalui Zodiac sign yang diaplikasikan guru di dalam kelas berjalan sesuai teori. Hasil kedua menunjukkan bahwa siswa memberikan respon positif, dan hasil ketiga adalah tentang hasil tulisan siswa. Tulisan siswa dianalisis dalam hal apakah isinya sesuai dengan judul, baik tidaknya penyusunan tulisan, penggunaan bahasa yang sesuai dengan descriptive, kosa kata sesuai, dan cara menyajikan tulisan oleh penulis. Kesimpulannya, implementasi ciri kepribadian seseorang melalui Zodiac sign dapat digunakan untuk media mengajar menulis descriptive, khususnya bagi kelas tujuh yang disebut sebagai pemula. Kata Kunci: Zodiac sign, ciri kepribadian, menulis, descriptive, respon siswa Abstract Writing is one of the important language skills that should be mastered by the students to convey their ideas or their opinion in written form. Moreover, writing is known as the most difficult skill in English. Writing process often makes students easily get bored. Here, the teacher is needed to maintain students’ motivation in order to keep students’ interest in writing. Zodiac sign is a media that can be used for teaching writing. It has personality traits and interesting pictures which can attract the students’ motivation in writing class. This research is aimed to describe the implementation of personality traits through Zodiac sign in teaching writing descriptive text to the seventh grade students, the students’ responses towards personality traits in the Zodiac sign, and the students’ writing task results. This research is a descriptive qualitative research. It used observation checklist, field note, interview, and also student’s task result as research instruments to gain data. The researcher endeavored to record the implementation of personality traits through Zodiac sign and describe it. The description is explained based on three objectives of the study; those are the implementation of personality traits through Zodiac sign to teach writing descriptive text , the students’ responses towards personality traits in the Zodiac sign, and also the students’ writing task results. After observing, the researcher described three results. The first result was regarding the implementation of personality traits through zodiac sign the teacher applied. The steps how the teacher applied the media in writing class. The second result was the students’ responses toward personality traits in the zodiac sign and it resulted positive responses. The third finding was the students’ writing task result that was analyzed by using ESL composition profile. It has five criteria; content which is appropriate with the topic, organization which is arranged well based on the generic structure, language use which is related to the language features, vocabulary which is appropriate to what have been listed by the teacher, and mechanics related to how well the writers write their writing. In conclusion, personality traits through zodiac sign could be used to teach writing descriptive text, particularly for seven graders as beginner English learner. It could be even used to keep students’ willingness in writing because of its steps. Keywords: Zodiac sign, personality traits, writing, descriptive text, students’ response.